An Analysis of Moral Message in Movie “LUCA” Using Semiotic Approach by Roland Barthes - Lalu Taufik Hasby Ash Shiddiq; Zainudin Abdussamad; Titik Ceriyani Miswaty (LPPM Universitas Bumigora Mataram, 2023)
This research explores the moral messages embedded in the animated movie